German-English Communication: A Cross-Cultural Challenge - Watzky, Sarah (Journal of International Students, 2013)
As an immigrant to the United States I have experienced many conflicts between my own German culture and the American culture I first encountered in 2007. While it was fairly easy to adapt to new cultural aspects such as food, lifestyle, education, and climate, the obstacle of language and communication was, and still is, more difficult to overcome for me. Research on cultural adaptation reflects my own struggles as well as those experienced by English speakers residing in Germany.